2016
DOI: 10.1038/nmicrobiol.2015.25
|View full text |Cite|
|
Sign up to set email alerts
|

Altered carbon turnover processes and microbiomes in soils under long-term extremely high CO2 exposure

Abstract: * There is only limited understanding of the impact of high p(CO 2 ) on soil biomes. We have studied a floodplain wetland where long-term emanations of temperate volcanic CO 2 (mofettes) are associated with accumulation of carbon from the Earth's mantle. With an integrated approach using isotope geochemistry, soil activity measurements and multi-omics analyses, we demonstrate that high (nearly pure) CO 2 concentrations have strongly affected pathways of carbon production and decomposition and therefore carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 67 publications
2
45
0
Order By: Relevance
“…Furthermore, as the functional omes display higher variability and sensitivity to perturbation 9,[11][12][13] , these variations may better reflect disease-related changes in host-microbiome interactions 14,15 . For this reason, the integration of metagenomic, metatranscriptomic and metaproteomic data is expected to yield important insights into the human microbiome 18 , as it has for environmental microbial consortia 19,20 .…”
mentioning
confidence: 99%
“…Furthermore, as the functional omes display higher variability and sensitivity to perturbation 9,[11][12][13] , these variations may better reflect disease-related changes in host-microbiome interactions 14,15 . For this reason, the integration of metagenomic, metatranscriptomic and metaproteomic data is expected to yield important insights into the human microbiome 18 , as it has for environmental microbial consortia 19,20 .…”
mentioning
confidence: 99%
“…Accumulation of SOM in soils on mofette fields relative to reference sites has been frequently reported (e.g., Beaubien et al, 2008;Beulig et al, 2015Beulig et al, , 2016Kerpen, 1960;Kool et al, 2007;Nowak et al, 2015;Rennert et al, 2011;Saßmannshausen, 2010). Accumulation of SOM is not only expressed by increased contents of soil organic carbon (SOC) in the topsoils, but also by the growth of hummocks, similar to those in peat lands, and the preservation of unaltered plant debris (Flechsig et al, 2008;Kerpen, 1960;Pätzold, 2009).…”
Section: Soil Organic Mattermentioning
confidence: 99%
“…Also the community structure of arbuscular mycorrhizal fungi is controlled by [CO 2 ], rather than by soil pH or available P (Maček et al, 2011). Very recently, Beulig et al (2016) reported that up to 67% of OM in soil on a mofette field originated from the assimilation of geogenic CO 2 by plant-primary production and subsurface-CO 2 fixation. They suggested that preservation and accumulation of almost unaltered SOM was facilitated by the permanent exclusion of meso-and macroscopic eukaryotes rather than by impaired biochemical potential for SOM decomposition.…”
Section: Soil Organic Mattermentioning
confidence: 99%
“…Acetate which is produced by acetogenic bacteria may then become a valuable substrate for Fe III , Mn III,IV and SO 2− 4 reducing microorganisms as well as acetoclastic methanogens . In addition, first analyses of the microbial communities in wetland soils of the Bublák mofette field in the Cheb Basin show that both bacteria and archaea are able to incorporate 13 C-labeled CO 2 (Beulig et al, 2015(Beulig et al, , 2016. Hence, an effect of the increased CO 2 concentrations on the composition of the microbial community seems very likely.…”
Section: Microbiological Backgroundmentioning
confidence: 99%